PERBEDAAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA YANG DIAJAR DENGAN MODEL KOOPERATIF TIPE NUMBERED HEAD TOGETHER DAN STUDENT TEAMS ACHIEVEMENT DIVISION - Tambunan, Mardiah; Siahaan, Sahat (Mahesa Research Center, 2020)
This study aims to determine differences in the ability to solve mathematical problems, in the class applied cooperative learning numbered head together and the student team achievement division. The ability to solve mathematical problems in terms of four aspects including understanding, planning, solving, and evaluating. The sample was chosen randomly from 12 classes to 2 classes. The two classes will be given different treatments. The data used for data analysis are pre-test data and post-test data. After testing these data, normality and homogeneity are stated. The results of hypothesis testing with a significance level, dk = n1 + n2 - 2 = 74, and ttable = 1.9953 obtained tcount = 4.433 so that -1.9953 <tcount> 1.9953. Thus H0 is rejected, which means that there are differences in the mathematical problem-solving abilities of students taught by using the NHT type cooperative model and by using the STAD type cooperative model in algebra material in class VII of the Pahlawan Nasional Middle School of Medan.